Morphometric characteristics of embryonic development Heterakis dispar isolated from geese - V. V. Stybel; O. B. Prijma (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2019)
Knowledge of the biological properties and ecological environment of the development of helminths, especially those that cause invasive diseases of animals and humans, is extremely important for understanding the epizootic aspects and clinical manifestations of invasions. Among the domestic and wild birds, one of the dominant ones is the group of parasitic nematodes of the genus Heterakis Dujardin, 1845. The aim of this study was to study the peculiarities of the embryonic development of Heterakis dispar, isolated from domestic geese, taking into account their morphological and metrical changes. Experimental cultivation of eggs isolated from gonads of H. dispar females to their invasive stage in the laboratory. Morphological and metric changes in the process of their embryogenesis were established. The picking of nematodes was performed by the method of complete helminthological opening of the caecum of dead or forcedly killed geese. It has been determined that the eggs of nematodes of domestic geese of H. dispar species under the temperature regime of 22 ºС undergo 4 stages of exogenous development: protoplast, crushing of blastomeres, formation of the larva of the first stage, formation of the larva of the second stage. At this temperature, the development of the parasites ended in 8 days, and the viability of the embryonic stages of the development of heteroxides was 79.33 ± 0.88%. In this case, developmental stoppage and death were observed in 20.67 ± 0.88% of eggs. The protoplast stage occurred within 1–18 days, the formation of two blastomeres – 2–4 days, the formation of the first stage larvae – 2–6 days, the formation of the second stage larvae – 4–8 days. In the process of exogenous development, the metric parameters of eggs of heterakises isolated from domestic geese change. Their sizes for cultivation from the stage of the protoplast to the larvae of the second stage are characterized by a significant decrease in width by 1.2 times and a simultaneous thinning of the shell by 1.1 times. Obtained data on the timing of the formation of invasive H. dispar eggs parasite in domestic geese, as well as their viability in the process of embryonic development can be used to improve the efficiency of species identification of isolated parasites by the results of scatoscopic studies of the bird.